PREVALENCE OF HEPATITIS B IN SELECTED ALASKAN ESKIMO VILLAGES - SCHREEDER, MARSHALL T.; BENDER, THOMAS R.; McMAHON, BRIAN J.; MOSER, MICHAEL R.; MURPHY, BERT L.; SHELLER, MARILYN J.; HEYWARD, WILLIAM L.; HALL, DAVID B.; MAYNARD, JAMES E. (Oxford University Press, 1983)
Schreeder, M.T., T. R. Bender (CDC, 225 Eagle St, Anchorage, AK 99501), B. J. McMahon, M. R. Moser, B. L. Murphy, M. J. Sheller, W. L Heyward, D. B. Hall and J. E. Maynard. Prevalence of hepatitis B in selected Alaskan Eskimo villages. Am J Epidemiol 1983;118:543–9. Sera collected in 1973–1975 from 3053 residents of 12 selected Alaskan Eskimo villages were tested for evidence of hepatitis B virus infection. Overall, hepatitis B surface antigen (HBsAg) was found in 6.4% of those tested. Evidence of hepatitis B infection (positive for HBsAg or antibody to hepatitis B surface antigen (anti-HBs)) varied considerably by village, from 4.6% to 69.9%, and increased with advancing age. The proportion with HBsAg was significantly higher in those under the age of 13 years, and the male/female ratio varied from 0.9 to 1.5 to 1.5 in the prepubertal, postpubertal-premenopausal, and postmenopausal age groups, respectively. The prevalence of hepatitis B e antigen (HBeAg) in HBsAg-posltive persons decreased with advancing age, and conversely, the prevalence of antibody to hepatitis B e antigen (antl-HBe) increased with age. Hepatitis B infection was found to be sporadically distributed, with great village-to-village variation and further variation by household within most villages. The high HBsAg and HBeAg seropositivity observed in children suggests that children are both more recently infected with hepatitis B and are more involved in hepatitis B transmission in these villages.